The Role of Islamic Boarding School as Socialization Agent of Ecological Values (A Case Study in Salaf-Modern Islamic Boarding School) - Sudjak Sudjak; Udji Asiyah; Ratna Azis Prasetyo (Sekolah Pascasarjana Universitas Brawijaya, 2017)
There are many studies on Islamic Boarding School, but the study which associating with Islamic boarding school as socialization agent of ecological values is still rare. This study aims to examine the understanding and concepts about the environment in Islamic Boarding School and the process of learning about religious values in the environment, but also want to know the implementation of the learning. Data collection was done first in-depth interviews to the Islamic Boarding School manager and the two primary data from the students (male and female). The study found that: First, most students perceived the concept of the environment and agreed to cleanliness association as part of faith. Secondly, a small percentage of male or female students are resistant to the environmental concept and their studies are inseparable from the existence of patriarchal culture carried on the contextual conditions that enclosed it, therefor the way of thinking, behaving is much influenced by the conditions in where they live. Third, the learning process associated with keeping the environment socialized through some yellow book recitation, outing class, artworks contest related to environmental hygiene and learning comfort, voluntary work. Fourth, most students agree to work once a week and agree on the existence of punishment if not participate in voluntary work. Fifth, actions by students associated with violations (cleanliness work), most of them proposed a fine or punishment.Keywords: Ecology, Islamic Boarding School, Punishment, Socialization